MTSS for Suicide Prevention and Intervention: Considerations for School Counseling Preparation - Emily Goodman-Scott; Jennifer Betters-Bubon; Rebecca Pianta (Teaching and Supervision in Counseling, 2022)
Youth mental health concerns have reached crisis-level with the American Academy of Pediatrics (2021) reporting a 51% increase for reported suicide attempts for 12-17 year old youth. School counselors play a pivotal role within the conversation on mental health and suicide specifically (ASCA, 2016; ASCA, 2020). In this article we outline how school counselors can organize their suicide prevention and intervention efforts with Multi-Tiered Systems of Support (MTSS), grounded in a model by Dr. Rebecca Pianta, as well as prioritizing culturally sustaining, antiracist practices, data, prevention, and screening in all tiers. Specifically, at Tier 1, school counselors educate stakeholders, including students, on the warning signs. While at Tiers 2 and 3, school counselors identify and support students at risk of suicide. We highlight ethical considerations throughout, in the context of the article Suicide Intervention in Schools: If Not School Counselors, Then Who?
Keywords: Suicide; multitier systems of support; school counseling